Evaluation of stress on metal surfaces by laser-induced breakdown spectroscopy. (21st October 2019) - Kang, Dongchan; Yoon, Sangwoo; Kim, Joohan
Abstract: In this study, we evaluated the feasibility of using laser-induced breakdown spectroscopy (LIBS) to determine the stress generated in metal materials by comparing measured stress levels with those determined by x-ray diffraction (XRD). Magnesium (Mg) alloy specimens underwent impact stress generated under ultrasonic peening. Stainless steel specimens were subjected to bending stress. The reference stress for each specimen was measured using XRD. LIBS measurements were performed to determine the correlation between stress distribution and the ratio of ionic to atomic spectral line intensity. The stress distribution from the surface to the interior of the ultrasonic-peened specimens measured by LIBS showed a similar tendency to that measured by XRD, but there was a difference in the maximum measurable depth. Additionally, the tensile and compressive stress distributions measured by LIBS on bending specimens showed similar trends to those of XRD. From these results, it was possible to measure the correlation between the stress state of the metal matrix and the spectral line strength of LIBS, thus confirming the potential for stress measurement using LIBS.